Análisis de Técnicas De Congelación De Semen Equino Empleadas En La Actualidad. Monografía (2023)
Seminal cryopreservation is a tool that allows the preservation and storage of genetic material for long periods of time, especially of males genetically superior, facilitating the work of artificial insemination since the semen horses have low motility and a high percentage of abnormal sperm cells, In addition to the fact that few stallions respond well to semen freezing, some of the causes of poor response to cryopreservation are the cryoprotectants used, the permeability of the spermatic membrane, the microbial load present in the ejaculate, the genetic factors. Sperm are subjected to different risks in the process of freezing, such as temperature, osmolarity that can cause damage to the structure of the cell membrane and osmotic stress, which generates an increase in cell permeability which leads to the entry of water, ions and cryoprotectants. The purpose of this collection literature is to recognize the different freezing techniques, advances, shortcomings in order to to improve the result that can be obtained after using cryopreservation protocols seminal